1984
DOI: 10.1002/bip.360230410
|View full text |Cite
|
Sign up to set email alerts
|

Electric birefringence study of the purple membrane of Halobacterium halobium

Abstract: SynopsisAn electric birefringence study was carried out on aqueous suspensions of the purple membrane of Halobacterium halobium. In addition to the characterization of both native and modified membrane samples, the dependence of electric birefringence on p H and ionic strength was also investigated. The results indicate that purple membrane shows electric birefringence a t a field strength a s low as 200 V/cm. T h e permanent dipole moment and polarizability ranged from 20,500 debyes and 1.01 X cm3 for a purpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These measurements have been used to characterize the electric moment of bacteriorhodopsin in its standard state. [5][6][7][8][9][10][11][12][13][14][15] Vectorial transport of protons by bacteriorhodopsin is controlled by a combination of different effects: light absorption induces a large pK change of the Schiff base and, thus, triggers a chain of proton-transfer reactions associated with changes in the protein structure. Changes of protein structure seem to be essential for the "relay" system, which directs the protons toward the extracellular side.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These measurements have been used to characterize the electric moment of bacteriorhodopsin in its standard state. [5][6][7][8][9][10][11][12][13][14][15] Vectorial transport of protons by bacteriorhodopsin is controlled by a combination of different effects: light absorption induces a large pK change of the Schiff base and, thus, triggers a chain of proton-transfer reactions associated with changes in the protein structure. Changes of protein structure seem to be essential for the "relay" system, which directs the protons toward the extracellular side.…”
Section: Introductionmentioning
confidence: 99%
“…A combined set of optical and electric parameters can be obtained by “molecular electrooptical” measurements. These measurements have been used to characterize the electric moment of bacteriorhodopsin in its standard state. …”
Section: Introductionmentioning
confidence: 99%
“…Electro-optical studies including measurements of the electric dichroism, birefringence and light scattering [8][9][10][11][12][13][14][15][16][17][18] demonstrated that purple membranes have a large permanent dipole moment in the direction perpendicular to the disk plane and a large induced dipole moment along the disk plane (Fig. 1).…”
Section: Structure and Electric Parameters Of Purple Membranesmentioning
confidence: 99%
“…[1][2][3] A favored model system for analysis has been bacteriorhodopsin, [4][5][6][7] because it is easily available and relatively stable. Its high anisotropy both with respect to electric and optical parameters [8][9][10][11][12][13][14][15][16][17][18] simplifies experimental characterization by electro-optical methods. 19,20 A standard approach to determination of electric parameters requires measurements of electrooptical data (dichroism, birefringence or light scattering) using both high frequency and DC-pulses.…”
Section: Introductionmentioning
confidence: 99%